2023
DOI: 10.3390/ijms241814125
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressing GmCGS2 Improves Total Amino Acid and Protein Content in Soybean Seed

Yuchen Zhang,
Qingyu Wang,
Yajing Liu
et al.

Abstract: Soybean (Glycine max (L.) Merr.) is an important source of plant protein, the nutritional quality of which is considerably affected by the content of the sulfur-containing amino acid, methionine (Met). To improve the quality of soybean protein and increase the Met content in seeds, soybean cystathionine γ-synthase 2 (GmCGS2), the first unique enzyme in Met biosynthesis, was overexpressed in the soybean cultivar “Jack”, producing three transgenic lines (OE3, OE4, and OE10). We detected a considerable increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…Among them, a total of 12,712 DEGs and 315 DAMs were identified [ 17 ]. Previous studies have demonstrated that overexpression of GmCGS2 leads to the upregulation of genes associated with the aspartic acid pathway, resulting in a substantial enhancement of total amino acid content and soluble protein levels within transgenic mature seeds [ 18 ]. In soybean, GmST05 may bind to GmSWEET10a in order to regulate seed size and protein content [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, a total of 12,712 DEGs and 315 DAMs were identified [ 17 ]. Previous studies have demonstrated that overexpression of GmCGS2 leads to the upregulation of genes associated with the aspartic acid pathway, resulting in a substantial enhancement of total amino acid content and soluble protein levels within transgenic mature seeds [ 18 ]. In soybean, GmST05 may bind to GmSWEET10a in order to regulate seed size and protein content [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high quality of soy protein, there has been a significant effort to improve the overall quality of protein content in soybean seed further. One example of progress in this area is the overexpression of the GmCGS2 gene in soybean seed to improve total protein content, including Met, a limiting amino acid in soybean [ 3 ]. Such breeding efforts will further enhance soybeans’ viability as a complete source of indispensable amino acids [ 4 ].…”
Section: Introductionmentioning
confidence: 99%